(untitled) (diségno, 2023)
The paper explores fala’s process of drawing, not as a daily routine, but as a source of breakthroughs and reconsiderations in established projects. It expresses a preference for drawings that exist for their intrinsic value, embodying intangible ideas, concepts, and reflections on form, space, and intelligence. The paper contends that a project unfolds through a plurality of drawings, highlighting the importance of single lines, collages wireframes, and renders. Referring to Charles Jencks’ concept of multivalence, it posits that each drawing influences and informs others, creating a multivalent experience that adds depth and meaning to the project. fala proposes that their built work is a byproduct of the drawing process, challenging the conventional view of the drawing’s dependence on clients, commissions, or sites. Each drawing is an independent entity, and the building itself is a form of drawing. Drawing parallels with Kazuo Shinohara’s perspective, fala argues that the act of communication and rhetoric surrounding architecture is as crucial as the built form itself. The paper posits that drawings and representations hold a social value that transcends the physical existence of the architecture. In conclusion, the paper presents a compelling argument for the autonomy of drawings, their multivalent interplay, and their central role in shaping the narrative and cultural significance of architectural practice, echoing the idea expressed by Kazuo Shinohara in viewing architecture as a beautifully choreographed fiction.